2020
DOI: 10.1136/jitc-2020-000778
|View full text |Cite
|
Sign up to set email alerts
|

M1hottumor-associated macrophages boost tissue-resident memory T cells infiltration and survival in human lung cancer

Abstract: BackgroundThe role of tumor-associated macrophages (TAMs) in determining the outcome between the antitumor effects of the adaptive immune system and the tumor’s anti-immunity stratagems, is controversial. Macrophages modulate their activities and phenotypes by integration of signals in the tumor microenvironment. Depending on how macrophages are activated, they may adopt so-called M1-like, antitumor or M2-like, protumor profiles. In many solid tumors, a dominance of M2-like macrophages is associated with poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 54 publications
9
112
0
Order By: Relevance
“…Interestingly, enrichment of a CD8 Trm signature was found in NSCLC patient samples containing higher levels of CXCL9 when compared with CXCL9 negative tumors. 30 This study suggested that M1 hot TAMs provide fatty acids to CD8+C-D103+Trm cells within the TME, a known mechanism for supporting peripheral CD8 T cell effector functions. 48 Further, CXCL9/10 expressing macrophages have been shown to directly promote effector CD8 T cell function.…”
Section: Cxcl9 Expressing Tams In Stem-like Cd8 T Cell Recruitment Anmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, enrichment of a CD8 Trm signature was found in NSCLC patient samples containing higher levels of CXCL9 when compared with CXCL9 negative tumors. 30 This study suggested that M1 hot TAMs provide fatty acids to CD8+C-D103+Trm cells within the TME, a known mechanism for supporting peripheral CD8 T cell effector functions. 48 Further, CXCL9/10 expressing macrophages have been shown to directly promote effector CD8 T cell function.…”
Section: Cxcl9 Expressing Tams In Stem-like Cd8 T Cell Recruitment Anmentioning
confidence: 80%
“… 25 A recent transcriptomic profiling study of TAMs from lung cancer patients also identified variable expression of inflammatory-macrophage-associated genes, most notably Cxcl9, Cxcl10 and Stat1 ascribed to an ‘M1 hot ’ phenotype. 30 Genes associated with this M1 hot state, including Cxcl9, correlated with increased survival and a higher density of intratumorous CD8 T cells indicating that human myeloid populations bearing a highly similar transcriptional state to murine Cxcl9 expressing-TAMs correlate with survival and accumulation of CD8 T cells in human cancer.…”
Section: Introductionmentioning
confidence: 92%
“…Nevertheless, our results demonstrate, at least in part, a potent role for M1 macrophages in shaping the immunostimulatory TME observed in cases with LG tumor budding. In a recent report by Garrido-Martin et al, the authors showed through single-cell transcriptomics in lung cancer, that while a majority of TAMs exhibited M2-like properties, 25% of cases exhibited macrophages with M1-like features, which were implicated in recruiting T cells via CXCL9 [ 54 ]. In our study, LS tumor budding cases from TCGA demonstrated significantly higher CXCL9 expression compared to HS patients suggesting that M1 macrophages are a key cellular source of CXCL9 in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that lung T RM cells were programmed to express IFITM3, which can protect them from secondary infection and improve survival ( 48 ). Except for cytokines and surface molecules, M1 hot tumor-associated macrophages can also contribute to the maintenance of lung T RM cells in tumor, possibly due to reduction in nutrition competition ( 49 ). In comparison with other tissue T RM cells that may persist for a long time or even a lifetime, lung T RM cells gradually disappear 4–5 months after infection.…”
Section: Development Of Lung T Rm Cellsmentioning
confidence: 99%